Interplay between pi-bridges and positions of branched alkyl groups of unsymmetrical D-A-D-pi-A squaraines in dye-sensitized solar cells: mode of dye anchoring and the charge transfer process at the TiO2/Dye/electrolyte interface - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Far-red-absorbing squaraines possessing high molar absorptivity (>10(5) M-1 cm(-1)) are being attracted as high-efficiency chromophores in dye-sensitized solar cells (DSSCs). A series of donor acceptor -donor-pi spacer-acceptor (D-A-D-pi-A) unsymmetrical squaraines, PSQ1-5, with indoline donor and squaric/cyanoacetic acid acceptor units, were designed for sensitized solar cells. For extending the absorption toward the near-infrared region (NIR) and controlling the orientation on the TiO2 surface, benzene (PSQ1 and PSQ2) and thiophene (PSQ3-5) 7r-spacers and out-of-plane branched alkyl groups at the indoline that are away (PSQ1, PSQ3, and PSQS) or near (PSQ2 and PSQ4) the anchoring group, respectively, were introduced. Dynamic aggregation tendency of PSQ1 and PSQ3 than that of their isomers systematically modulates the orientation on the TiO2 surface, which in turn enhances photovoltaic performance. Absorptance on a thin transparent TiO2 film shows a visible-to-NIR response with an onset around 800 nm for PSQ3-5. Although there is resemblance in electrochemical redox levels, their high injection efficiency and recombination resistance differentiated impact on the way of anchoring and the dihedral angle between D-A-D units and g-spacers. DSSCs sensitized with PSQS achieved a PCE of 8.15% under simulated AM 1.5G illumination (100 mW cm(-2)), with the current density (j) and open-circuit voltage (Voc) of 19.73 mA cm(-2) and 630 mV, respectively. A clear comparison of the incident-photon-to-current conversion efficiency versus the light-harvesting efficiency correlates the structure-property relationship with J obtained for PSQ dyes. Electrochemical impedance spectroscopy was carried out to examine the TiO2/dye/electrolyte interface for further confirmation of the enhanced PCE of top-se-alkylated PSQS over that of other dyes.
Keywords: D-A-D-pi-A framework; dye-sensitized solar cell; H- and J-type aggregation; orientation of dyes; static/dynamic aggregates; unsymmetrical squaraine

Molecular control of the band edge movement and the recombination process in donor-acceptor hemicyanine-sensitized solar cells - Karjule, Neeta; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Journal of Physical Chemistry C, 2017)
The presence of downward shift in the band edge and the recombination reactions in the hemicyanine-sensitized solar cell reduces the open-circuit potential (V-oc) and the short-circuit current density (J(sc), which in turn decreases the dye cell performance. Choosing either an electrolyte possessing minimum overpotentials or a systematic dye design which can efficiently suppress the diffusion of charged species toward the TiO2 can improve the overall power conversion efficiency (PCE). Here, a series of donor acceptor (D-A) hemicyanine dyes were synthesized utilizing a planar heterotriangulene (HT) or triphenylamine (TPA) donor and alkyl-functionalized indolium carboxylic acid acceptor unit. By introducing strong HT donor instead of TPA, the photophysical, and electrochemical properties of D-A dyes are significantly modulated. The strong donor nature of HT and effective passivation of surface by hydrophobic alkyl chains close to the anchoring group for NC3 dye exhibits an average PCE of 4.34% with a V-oc of 0.416 V, J(sc) of 20.04 mA cm(-2), and fill factor (ff) of 52.03% under simulated AM 1.5G illumination (100 mW cm-2) without 3 alpha,7 alpha-adihydroxy-5 beta-cholic acid coadsorbent (CDCA). The intrinsic dipole of the hemicyanine dye and the presence of Li+ ions in iodide/triiodide redox couple without tert-butylpyridine (TBP) additive induces a downward shift in conduction band edge (E-CB) of TiO2. By rational molecular design, the extend of shift in E-CB is controlled and enhanced the V-oc. Electrochemical impedance spectroscopy (EIS) studies revealed the high charge transfer resistance (R-ct) and long lifetime (tau) of injected electrons in HT-based dyes than that of TPA derivatives, which provide insight into the passivation of Li+ and I- ions by current D-A dye design possessing alkyl functionalities to increase both the J(sc) and V-oc.

Orthogonally functionalized donor/acceptor homo- and heterodimeric dyes for dye-sensitized solar cells: an approach to introduce panchromaticity and control the charge recombination - Sil, Manik Chandra; Sudhakar, Vediappan; Kavungathodi, Munavvar Fairoos Mele; Punitharasu, Vellimalai; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Organic dyes possessing conjugated pi-framework forms closely packed monolayers on photoanode in dye-sensitized solar cell (DSSC), because of the limitation to control the orientation and the extend of intermolecular pi-pi interaction, self-aggregation of dyes leads to reduced cell performance. In this report, a series of homodimeric (D-1-D-1, and D-2,-D-2) and heterodimeric (D-1-D-2 and D-2-D-4) donor/acceptor (D/A) dyes containing spiroBiProDOT pi-spacer were designed and synthesized by utilizing Pd-catalyzed direct arylation reaction and correlates the device performance with monomeric dyes (D-1 and D-2). Both the thiophenes (pi-spacer) of spiroBiProDOT were functionalized with same or different donor groups which led to homodimeric and heterodimeric chromophores in a single sensitizer. The homodimeric spirodye D-1-D-1 showed higher power conversion efficiency (PCE), of 7.6% with a V-oc and J(sc) of 0.672 V and 16.16 mA/cm(2), respectively. On the other hand, the monomeric D-1 exhibited a PCE of 3.2% (V-oc of 0.64 V and J(sc) of 7.2 mA/cm(2)); which is lower by 2.4 fold compared to dimeric analogue. The spiro-unit 20 provides flexibility between the incorporated chromophores to orient on TiO2 due to four sp(3)-centers, which arrest the molecular motions after chemisorption. This study shows a new molecular approach to incorporate two chromophores in the dimeric dye possessing complementary absorption characteristics toward panchromatic absorption. The attenuated charge recombination at TiO2/Dye/redox couple interface in case of D-1-D-1, owing to better passivation of TiO2 surface, was elucidated through impedance analysis. The FT-IR spectrum of D,-D, adsorbed on TiO2 film indicated both the carboxylic units were involved in chemisorption which makes strong coupling between dye and TiO2.

Fused fluorenylindolenine-donor-based unsymmetrical squaraine dyes for dye-sensitized solar cells - Bisht, Rajesh; Sudhakar, Vediappan; Kavungathodi, Munavvar Fairoos Mele; Karjule, Neeta; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2018)
A series of four unsymmetrical squaraine dyes, XSQ1-4, were synthesized using a fused fluorenylindolenine-based donor unit for dye-sensitized solar cells (DSSCs). The fused structure of fluorenylindolenine helped in moving the absorption toward the near-infrared (NIR) region, and the two sp(3)-C centers available on this donor were utilized to incorporate out-of-plane alkyl chains in opposite directions to control the dye-dye interactions on the TiO2 surface. High extinction coefficient (epsilon >= 10(5) M-1 cm(-1)) for absorbing NIR photons and suitable highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels with respect to the conduction band of TiO2 and electrolyte for charge injection and dye regeneration processes, respectively, make these dyes potential sensitizers for DSSCs. Introduction of branched alkyl groups in the pi-framework helped in controlling dye aggregation to reduce exciton quenching and assisted in TiO2 surface passivation to avoid the charge recombination process. Furthermore, having a naphthyl group on the indole part of the anchoring group containing segment helped to red-shift the absorption spectrum of dyes 15 nm toward the NIR region (XSQ3-4). Among all of the dyes under investigation, XSQ2 gave the best photovoltaic performance, having a short-circuit current density (J(SC)) of 13.99 mA cm(-2), open -circuit voltage (V-OC) of 0.66 V, and a fill factor (ff) of 0.71, with a device performance (eta) of 6.57%. Electrochemical impedance spectroscopy revealed higher electron lifetime on TiO2 for XSQ2, which helps to avoid the charge recombination process.
Keywords: Dye-sensitized solar cells; fluorenylindolenine; H- and J-type aggregation; NIR absorption; out-of-plane alkyl groups; squaraine dyes

Homo- and heterodimeric dyes for dye-sensitized solar cells: panchromatic light absorption and modulated open circuit potential - Sil, Manik Chandra; Sudhakar, Vediappan; Singh, Ambarish Kumar; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ChemPlusChem, 2018)
The design of dyes for panchromatic light absorption has attracted much attention in the field of dye-sensitized solar cells (DSSCs). An approach to enhance panchromatic light absorption utilizes mixtures of complementary light-absorbing dyes as well as dyes with specific anchoring groups that facilitate interfacial charge transfer with TiO2. Dipole-dipole interactions between the dye molecules on the surface broaden the spectrum, which results in decreased DSSC device performance. However, controlled aggregation of dyes results in broadening the spectral profile along with enhanced photocurrent generation. To control the dye-dye interaction, dimeric dyes with different dipole lengths D-1-D-sq, D-sq-D(sq)were systematically designed and synthesized. The photophysical and electrochemical properties were evaluated and the E-HOMO and E-LUMO levels were determined; these energy levels determines the electron injection from E-LUMO of the dye to E-CB of TiO2 and regeneration of oxidized dye by the electrolyte, respectively. The absorption spectra of D-sq-D-sq, D-1-D-sq were broadened in solution compared to model dye D-sq; this indicates that the dye-dye interaction is prominent in solution. In D-1-D-sq excitation energy transfer between photoexcited D-1 and D-sq was explained by using Forster resonance energy transfer (FRET). The homodimeric dye showed a device performace of 2.8 % (V-oc 0.607, J(sc) 6.62 mA/cm(2), ff 69.3 %),whereas the heterodimeric dye D-1-D-sq showed a device performance of 3.9 % (V-oc 0.652 V, J(sc) 8.89 mA/cm(2), ff 68.8 %). The increased photocurrent for D-1-D(sq)is due to the panchromatic IPCE response compared to D-sq-D-sq. The increased V(oc)is due to the effective passivation of the TiO2 surface by the spirolinker, and the effective dipole moment that shifts the conduction band on TiO2. Hence, the open circuit potential, V-oc, for the devices prepared from D-sq, D-1-D-sq and D-sq-D(sq)were systematically modulated by controlling the intermolecular pi-pi and intramolecular dipole-dipole interactions of the dimeric dyes.

Indenoquinaldine-based unsymmetrical squaraine dyes for near-infrared absorption: investigating the steric and electronic effects in dye-sensitized solar cells - Bisht, Rajesh; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Chemistry-A European Journal, 2018)
A series of near-infrared (NIR)-responsive unsymmetrical squaraine dyes (ISQ1-3) incorporating a fused indenoquinaldine-based donor have been designed and synthesized. C-12 alkyl chains were incorporated at the sp(3)-hybridized carbon center of the indene unit of the indenoquinaldine in an out-of-plane orientation to control dye aggregation on the surface of titanium dioxide, and indole (ISQ1), benzo[e]indole (ISQ2), and quinoline (ISQ3) moieties were included as the donor component bearing the anchoring carboxy group to extend the absorption in the NIR region and to systematically study the effect of the electronic modification on the performance of dye-sensitized solar cells (DSSC). All the dyes exhibit intense absorption (epsilon >= 10(5) m(-1) cm(-1)) in the NIR region, and the dye-adsorbed TiO2 films exhibit broad panchromatic absorption. The incident photon-to-current efficiency (IPCE) spectrum of the ISQ3-based DSSC device displays a panchromatic IPCE response up to 880 nm. Additionally, the ISQ3-sensitized device provides the best efficiency of 4.15% with a short circuit current density (J(SC)) of 10.02 mA cm(-2), open-circuit voltage (V-OC) of 0.58V, and fill factor (ff) of 72% in the presence of 10 equivalents of 3 alpha,7 alpha-dihydroxy-5 beta-cholanic acid (CDCA). Electrochemical impedance spectroscopy analysis showed attenuated charge recombination in the ISQ3-sensitized DSSC, which contributes to its higher value of V-OC compared with the other dyes.

Self-assembly of Cis-configured squaraine dyes at the TiO2-dye interface: far-red active dyes for dye-sensitized solar cells - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2018)
To synergize both steric and electronic factors in designing the dyes for dye-sensitized solar cells, a series of cis-configured unsymmetrical squaraine dyes P11-P15 with suitably functionalized alkyl groups and squaric acid units containing the electron-withdrawing groups were synthesized, respectively. These dyes capture the importance of (i) the effect and position of branched alkyl groups, (ii) mono- and di-anchoring groups containing dyes, and (iii) further appending the alkyl groups through the cyanoester vinyl unit on the central squaric acid units of DAD-based cis-configured squaraine dyes. All the above factors govern the controlled self-assembly of the dyes on the TiO2 surface which helps to broaden the absorption profile of the dyes with an increased energy-harvesting process. With respect to the position of the branched alkyl groups, dye P11 with the sp(3)-C and N-alkyl groups away from the TiO2 surface showed a better device efficiency of 5.98% (J(sc) of 14.46 mA cm(-2), V-oc of 0.576 V, and ff of 71.8%) than its positional isomer P12 with 3.45% (J(sc) of 8.78 mA cm(-2), V-oc of 0.554 V, and ff of 70.9%). However, with respect to the dyes containing mono- and di-anchoring groups, P13 with two anchoring units exhibited a superior device performance of 7.58% (J(sc) of 17.12 mA cm(-2), V-oc of 0.618 V, and ff of 71.7%) in the presence of optically transparent co-adsorbent CDCA (3 alpha,7 alpha-dihydroxy-5 beta-cholanic acid) than dyes P11 and P12.

Effect and position of spiro-bipropylenedioxythiophene pi-spacer in donor-pi-spacer-acceptor dyes for dye-sensitized solar cell - Sil, Manik Chandra; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Dyes and Pigments, 2019)
Improper orientation and self-assembly of dyes on TiO2 surface are the main disadvantages at the dye-TiO2 interface that governs both charge injection and dye regeneration processes. In this report, a series of homo spiro-dimeric donor-pi-spacer-acceptor (D-pi-A) dyes based on bithiophene and terthiophene spacers with two-anchoring group containing dyes, TT1, T1T, TT1T were designed and synthesized by Pd-catalyzed successive Suzuki coupling followed by direct arylation reactions. The position of branching centre in TT1 and T1T was systematically varied, where the spiro unit was placed near and away from the anchoring carboxylic acid unit, respectively. The dimeric spiro-dye T1T showed device performance, which is 1.6 fold higher than its structural isomeric analogue TT1, of 3.9% with a V-oc and J(sc) of 0.593 V and 9.09 mA/cm2, respectively, whereas for the isomeric analogue TT1 a device performance of 2.45% (V-oc of 0.568 V and J(sc) of 6.25 mA/cm2) under simulated 1 Sun (100 mW/cm2) condition. The improved Voc for the dye T1T compared to TT1 dye was ascribed to the dipole moment exerted by the dyes on TiO2 surface. Further the PCE of 4.16% (V-oc 0.589 V, J(sc) 9.79 mA/cm2 respectively) maximum was observed, when an extra thiophene unit was inserted in between the donor and pi-spacer in dye TT1T. The shifting the position of branching spiroBiProDOT pi-spacer makes an impact on the device performance by synergistically enhancing both Voc and Jsc.
Keywords: CDCA; D-pi-A Spiro dye; Dye aggregation; dye-sensitized solar cell; spiroBiProDOT spacer

pi-Extended cis-configured unsynimetrical squaraine dyes for dye-sensitized solar cells: panchromatic response - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2019)
{Light absorbing sensitizer is the heart of the third generation photovoltaic technologies such as dye sensitized solar cells. Despite possessing large extinction coefficients for the metal-free organic dyes, the light harvesting efficiency is limited with the narrow absorption 20 profile in either visible or NIR regions of the solar spectrum. Though monolayer formation of organic sensitizers on semiconducting metal oxide surface leads to dye-dye interaction that leads to broadening the absorption profile, the contribution of the aggregated state to the power conversion process is found out to be poor. Here, we have engineered far-red active pi-extended cis-configured unsymmetrical squaraine dyes with carboxylic acid and cycnoacetic acid as anchoring groups with controlled aggregation and panchromatic light absorption by including the steric and electronic factors. The presence of sp(3)-C (out-of-plane) and N-alkyl (in-plane) groups played an important role in modulating the assembly of the dyes on the TiO2 electrode; the cis-squaraine unit helps to extend the conjugation in the NIR region besides enhancing the visible transition and the incident photon-to-current conversion efficiency profile that showed the importance of anchoring groups for the panchromatic response. Dye PSQ10 showed solar-to electric conversion with an onset of 850 nm with the device performance of 7.0% (V-oc = 0.581 V, J(sc) = 17.06 mA/cm(2)
Keywords: cis-squaraine dyes; Dye aggregation; Dye-sensitized solar cells; extended far-red absorption; panchromatic response

Alkyl-group-wrapped unsymmetrical squaraine dyes for dye-sensitized solar cells: branched alkyl chains modulate the aggregation of dyes and charge recombination processes - Singh, Ambarish Kumar; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2020)
Electron transfer processes at the interfaces dictate the factors that improve the photovoltaic parameters, such as open-circuit voltage (V-oc) and short-circuit current (J(sc)), of a dye-sensitized solar cell device, besides selection of a set of suitable anode, dye, electrolyte, and cathode materials. An inefficient charge injection process at the dye-TiO2 interface and charge recombination at the TiO2-dye/electrolyte interface have detrimental effects on improving both J(sc) and V-oc. Hence, tailoring the factors that govern the improvement of J(sc) and V-oc will be an ideal approach to get the desired sensitizers with good device efficiencies. Squaraines are far-red-active zwitterionic dyes and have a high molar extinction coefficient along with unique aggregation properties due to the large dipole moment associated with them. Here, we report a series of unsymmetrical squaraine dyes, SQS1 to SQS6, with systematic variation of alkyl groups at the sp(3)-C and N-atoms of the indoline unit that is away from the anchoring group to control the dye-dye interactions on the TiO2 surface. The branched alkyl groups help in modulating the self-assembly of sensitizers on the TiO2 surface, besides passivating the surface that helps avoid the charge recombination processes. Light harvesting efficiency and cyclic voltammetry studies of dye-sensitized TiO2 electrodes indicate that the aggregation and charge hopping process between the dye molecules can be modulated, respectively, by systematically increasing the number of carbon atoms in the alkyl groups. Such a variation in the branched alkyl group helps enhance V-oc from 672 (SQS1) to 718 mV (SQS6) and J(sc) from 7.95 (SQS1) to 12.22 mA/cm(2) (SQS6), with the device efficiency ranging from 3.82% to 6.23% without any coadsorbent. Dye SQS4 achieves the highest efficiency of 7.1% (V-oc = 715 mV, J(sc) = 13.05 mA/cm(2)) with coadsorbent chenodeoxycholic acid (CDCA) using an iodine (I-/I-3(-)) electrolyte compared to its analogues. An analysis of the incident photon-to-current efficiency profiles indicates that the major contribution to photocurrent generation is from the aggregated squaraine dyes on TiO2.
Keywords: aggregation of dye; charge injection; charge recombination; Dye-sensitized solar cells; unsymmetrical squaraines